Controlled fluorination of a-C:F:H films by PECVD of ethylene-hexafluorobenzene mixtures - Lopes, Bruno Bellotti [UNESP]; Davanzo, Celso U.; Schreiner, Wido; Durrant, Steven F. [UNESP] (Elsevier B.V. Sa, 2008)
Highly fluorinated plasma polymers are chemically inert,acid resistant and have low friction coefficients, thereby being useful in chemical laboratories and for tribological applications. Here we report the plasma polymerization of ethylene-hexafluorobenzene mixtures by PECVD. The principal parameter of interest is the proportion of C(6)F(6) in the feed, R(F). Films were analyzed using near-normal and grazing-angle Infrared Reflection Absorption Spectroscopy (IRRAS), the latter being particularly useful for detecting modes not usually observed at near-normal incidence. The presence of CH and CF(x) (x=1 to 2) groups was thus confirmed in films deposited with R(F)>= 40%. Depending on R(F) IRRAS also revealed the presence of -CH(x) (x=1 to 3) -C=C, -C=O and phenyl rings. Deconvolution of C is spectra obtained by X-ray Photoelectron Spectroscopy (XPS) confirmed the presence of CH, CF and CF(2) groups in films deposited with R(F)>= 40%. Atomic ratios of F:C calculated from the XPS spectral data show that the degree of fluorination rises with increasing RF Some unbound fluorine is present in the films. Post-deposition reactions account for the presence of oxygen (similar to 5%) in the films. Surface energies, determined from contact angle measurements, fall with increasing R(F). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: PECVD; Hexafluorobenzene; Thin films; XPS; IRRAS